The Midwest Exercise Trial for the Prevention of Weight Regain: MET POWeR - Donnelly, Joseph E. (2013)
Weight reduction in overweight and obese individual’s results in physiological and behavioral changes that make the prevention of weight regain more difficult than either initial weight loss or the prevention of weight gain. Exercise is recommended for the prevention of weight regain by both governmental agencies and professional organizations. To date, the effectiveness of exercise recommendations for the prevention of weight regain has not been evaluated in a properly designed, adequately powered trial. Therefore, we will conduct a randomized trial to evaluate the effectiveness of 3 levels of exercise on the prevention of weight regain, in initially overweight and obese sedentary men and women. Participants will complete a 3 month weight loss intervention of decreased energy intake (EI) and increased exercise (100 minutes/week). Participants achieving clinically significant weight loss (≥ 5% of initial weight), will then be randomly assigned to 12 months of verified exercise at 3 levels (150, 225 or 300 minutes/week). This study will evaluate: 1) the effectiveness of 3 levels of exercise on the prevention of weight regain over 12 months subsequent to clinically significant weight loss (≥ 5%); 2) gender differences in weight regain in response to 3 levels of exercise; and 3) potential compensatory changes in daily physical activity (PA) and EI on weight regain in response to 3 levels of exercise. Results of this investigation will provide information to develop evidenced based recommendations for the level of exercise associated with the prevention of weight regain.